International Relations Ingredients in Utopia: An Analysis of Callenbach’s Ecotopia - K. C., Chandra Bahadur (Interdisciplinary Journal of Management and Social Sciences, 2023)
This research paper aims to investigate the ingredients of international relations in Ernest Callenbach’s utopian novel Ecotopia (1975). First, this paper analyses the concepts of Utopia and International Relations. Then, it explains and finds out that Ecotopia, an earth-friendly place that has seceded from the U.S. for about two decades because of its involvement in nature degradation activities, has cut off its relations with the U.S., but Ecotopia is not isolated from the rest of the world. The U.S. sends William Weston, a top international affairs reporter, and the protagonist, to make eroded diplomatic relations with Ecotopia amicable. But he finds Ecotopia as a live-worth place and decides to live there permanently. Ecotopia has established relations with other nations politically, economically as well as culturally. Except with the U.S., Ecotopia is involved in importing iron from other nations and exporting cultural artifacts to them. Ecotopian Government has applied a deterrence policy with the U.S., so it has run nuclear fission plants though such projects are against the ethics of a utopian nation. Ecotopians blame America for being an imperialist nation and waging wars against different nations. They believe that big nations must secede further into small nations so that they can manage their natural resources making them earth-friendly. This research concludes that a utopian work also includes different ingredients of international relations.